The effect of pressure cooking on the microstructure and expansion of fish cracker ('keropok') - Kyaw, Z.Y.; Cheow, C.S.; Yu, S.Y.; Dzulkifly, M.H. (Food and Nutrition Press, 2001)
The effect of pressure cooking on microstructure of wheat and tapioca starch in keropok gel and expansion of fried keropok slices were studied. The morphology of the starch granules in the keropok gel at different steaming temperature was examined using scanning electron microscopy (SEM). Linear expansion of keropok made with wheat starch increased with increasing steaming temperature, but that of keropok made with tapioca starch decreased with increasing steaming temperature. The linear expansion results correlate with the sensory evaluation of the products. fs25.